The relationship of self-identity to school bullying among adolescents (a field study on a research sample in the schools of Gdaidat Artuz in Damascus Countryside ( (Damascus University Journal of arts and humanities sciences, 2025)
The present study aimed at knowing the relationship between self identity and school bullying. The study depends on the descriptive analytical. The study tools were a scale to measure the self concept, and a scale to measure the school bullying. The study sample consists of (130) male and female students from the eighth grade students in the schools of Damascus. The most important findings of the study were: There were negative correlations statically significant between the scores of the students on the scale of the self - identity and the scores of the students on the scale of the school bullyin, There was no high level of self- identity  and school bullyingamong the research sample, There weren't difference between the mean scores of the students on the scale of the self identity due to the sex variable, There were difference between the mean scores of the students on the scale of the school bullying due to the sex variable favor for the male students
Keywords: Self Identity; School Bullying; Students From The Second Basic Education School